LEGAL REGULATION AUTHORITY TO GRANT PERMITS ON THE VENTURE CAPITAL COMPANY - Indradewi, Anak Agung Sagung Ngurah (Legality : Jurnal Ilmiah Hukum, 2019)
The authority to grant permits to venture capital companies has a dualism of authority. The Financial Services Authority and the Ministry of Finance both have the authority to give licenses to venture capital companies. It can be seen that there are overlaps or conflicts of authority in this case institutional or legal institutions are authorized to give permission to venture capital companies. A norm of conflict over the authority of granting permission to venture capital companies, namely the Minister of Finance Regulation No. 18 / PMK.010 / 2012 concerning Venture Capital Companies (VCC) in Article 11 paragraph (1) VCCs are established in the form of limited liability companies or cooperatives, Article 12 paragraph (1) Legal entities as referred to Article 11 paragraph (1) the which carry out activities as VCC must first obtain a business permit from the Minister. Whereas the Financial Services Authority (FSA) Regulation No. 34 / POJK.05 / 2015 Concerning Business Licensing and Institutional Venture Capital Companies, in article 3 Paragraph (1) Every party conducting business activities for VCC or Sharia VCC must obtain a business license from the FSA. On the one hand the Ministry of Finance has the authority to issue a Venture Capital Company permit, but on the other hand the Financial Services Authority is also authorized to issue a Venture Capital Company permit. It is understandable that the position of state institutions and / or institutions of the Ministry of Finance with the Financial Services Authority is equal, in this case the same law was born, namely Law Number 39 of 2008 concerning the State Ministry and Law No. 21 of 2011 concerning Institutions Financial Services Authority.